2003
DOI: 10.1007/s00467-003-1241-y
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of water transport in the rabbit proximal tubule

Abstract: Water transport across cell membranes is a fundamental biological problem. In the kidney, many nephron segments have mechanisms for transporting large quantities of water with minimal energy input. The proximal tubule reabsorbs two-thirds of the glomerular filtrate with a small transepithelial osmotic gradient as the driving force. In the adult proximal tubule, this is accomplished by the expression of aquaporin 1 (AQP1), the water channel located on the apical and basolateral membranes of the proximal tubule.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…At birth, water is rapidly absorbed from the lungs in preparation for alveolar gas exchange in which AQP1 may have a role (52). In the juxtamedullary proximal convoluted tubules (PCT) from neonatal rabbits, expression of AQP1 is lower than in the adult PCT, whereas osmotic permeability of the PCT is approximately the same as in adults (96). This may suggest that tubule properties other than AQP1 expression may be important for neonatal PCT (96).…”
Section: Function and Regulation Of Aqps In Birds And Other Vertebratesmentioning
confidence: 99%
“…At birth, water is rapidly absorbed from the lungs in preparation for alveolar gas exchange in which AQP1 may have a role (52). In the juxtamedullary proximal convoluted tubules (PCT) from neonatal rabbits, expression of AQP1 is lower than in the adult PCT, whereas osmotic permeability of the PCT is approximately the same as in adults (96). This may suggest that tubule properties other than AQP1 expression may be important for neonatal PCT (96).…”
Section: Function and Regulation Of Aqps In Birds And Other Vertebratesmentioning
confidence: 99%
“…This text will refer heavily to the previous work done by Cruise and Brewer as stated above. The epithelium of the proximal tubule is made up of a single layer of cells supported by a basement membrane (Quigley et al, 2003). Transitions between segments are gradual compared to other mammals such as the dog and rat (Kaissling and Kriz, 1979).…”
Section: Kidneymentioning
confidence: 99%
“…This occurs in a nearly isoosmotic manner due to the high water permeability of this nephron segment provided by the abundance of aquaporin-1 (AQP1), the water channel in the kidney proximal tubule (1,18,26). The functional aspects of water transport in the proximal tubule during development have recently been studied and reviewed (21)(22)(23)(24)(25). In vitro microperfusion revealed that the osmotic water permeability coefficient (P f ) of the proximal tubule is higher in the neonatal rabbit than that in the adult (21).…”
Section: Introductionmentioning
confidence: 99%